Experimental study on recoverable thermal energy from low thermal inertia exhaust heat recovery unit - Osman, A. (SAGE Publications Inc., 2021)
Modern engines in general waste plenty of heat to the exhaust gas and coolant. Considering that daily driving consists of frequent cold start, idling, and part load driving within short driving distances, the potentials to recover heat from high enthalpy exhaust gas are limited. In recovering heat from low enthalpy exhaust gas, a low thermal inertia exhaust heat recovery unit (EHRU) with no heat transfer fins is proposed to be integrated to the simplified split cooling circuit used in the earlier studies. This lightweight, compact and simple EHRU concept made of machined steel plate is targeted for naturally aspirated engines that are still being widely used worldwide. Cooler coolant feed from the bottom of the cylinder blockâs water jacket rear end provided large temperature difference between the coolant and exhaust gas. In evaluating its effectiveness in speeding up the recovered heat availability for reuse, a 1.3 l passenger car equipped with strategically placed multiple thermocouples and flow meters was tested using NEDC test. From the experiments and classical analysis, the recovered thermal energy was available in just 25 s after cold start. The study also provided a new direction on the design of EHRU and its integration into an engine. Â© The Author(s) 2021.